The use of three-dimensional endoscope in transnasal skull base surgery: A single-center experience from China - Xin, Guo; Liu, Yajing; Xiong, Yicheng; Xie, Shenhao; Luo, Hai; Xiao, Liming; Wu, Xiao; Hong, Tao; Tang, Bin (Frontiers in Surgery, 2022)
Objective The development of skull base surgery in the past decade has been influenced by advances in visualization techniques; recently, due to such improvements, 3D endoscopes have been widely used. Herein, we address its effect for transnasal endoscopic skull base surgery. Methods A total of 63 patients who under endoscopic endonasal surgery (EES) with 3-D endoscope were retrospectively reviewed, including pituitary adenomas, craniopharyngiomas, meningiomas, Rathke’s cleft cysts, and chordomas. According to different lesions, transsellar approach (24 cases), transsphenoidal–transtuberculum approach (14 cases), transclival approach (6 cases), and transpterygoid approach (19 cases) were selected. Results Total removal of tumors was achieved in 56 patients (88.9%) and subtotal removal in 7 cases (11.1%). Complications included diabetes insipidus in seven patients (11.1%), cerebrospinal fluid (CSF) leakage in two patients (3.2%), major vascular injury occurred in one patient (1.6%), cranial nerve injury in nine patients (14.3%), and meningitis in two patients (3.2%). There was no mortality in the series. All patients recovered and were back to normal daily life, and no tumor recurrence or delayed CSF leakage was detected during the follow-up (2–13 months, mean 7.59 months). Conclusions Via 3D EES, it improved depth perception and preserved important neurovascular tissue when tumors were removed, which is important for improving the operative prognosis.